Hederagenin Protects PC12 Cells Against Corticosterone-Induced Injury by the Activation of the PI3K/AKT Pathway - Lin, Ruohong; Liu, Linlin; Silva, Marta; Fang, Jiankang; Zhou, Zhiwei; Wang, Haitao; Xu, Jiangping; Li, Tiejun; Zheng, Wenhua (Frontiers in Pharmacology, 2021)
Depression is a prevalent psychiatric disorder and a leading cause of disability worldwide. Despite a variety of available treatments currently being used in the clinic, a substantial proportion of patients is unresponsive to these treatments, urging the development of more effective therapeutic approaches. Hederagenind (Hed), a triterpenoid saponin extracted from Fructus Akebiae, has several biological activities including anti-apoptosis, anti-hyperlipidemic and anti-inflammatory properties. Over the years, its potential therapeutic effect in depression has also been proposed, but the information is limited and the mechanisms underlying its antidepressant-like effects are unclear. The present study explored the neuroprotective effects and the potential molecular mechanisms of Hederagenin action in corticosterone (CORT)-injured PC12 cells. Obtained results show that Hederagenin protected PC12 cells against CORT-induced damage in a concentration dependent manner. In adittion, Hederagenin prevented the decline of mitochondrial membrane potential, reduced the production of intracellular reactive oxygen species (ROS) and decreased the apoptosis induced by CORT. The protective effect of Hederagenin was reversed by a specific phosphatidylinositol-3-kinase (PI3K) inhibitor LY294002 and AKT (also known as protein kinase B) inhibitor MK2206, suggesting that the effect of Hederagenin is mediated by the PI3K/AKT pathway. In line with this, western blot analysis results showed that Hederagenin stimulated the phosphorylation of AKT and its downstream target Forkhead box class O 3a (FoxO3a) and Glycogen synthase kinase-3-beta (GSK3β) in a concentration dependent manner. Taken together, these results indicate that the neuroprotective effect of Hederagenin is likely to occur via stimulation of the PI3K/AKT pathway.